Just transitions promise and contestation - Stevis, Dimitris (Cambridge University Press, 2023)
This Element aims to place just transition in the dynamics of the world political economy over the last several decades and to offer an overview of the varieties of just transitions based on an analytical scheme that focuses on their breadth, depth and ambition
Keywords: Social justice / Environmental aspects; Sustainable development / Social aspects; Equality